Identifying a Student as a Subject of Educational Activity: Methodology and Web-based Application - Chernova, Natalya; Akhunzyanova, Raisa; Alatrani, Abbas; Mustafina, Jamila (2023 15th International Conference on Developments in eSystems Engineering (DeSE), 2023)
The purpose of the article is to outline the core concepts of a subject intension, molding and development, being also important to the intensification of AI-enhanced university education. Cognitive development clearly suggests that it is inseparably linked with speech intellectual activity and because of it is reality reflection as if refracted in the light of linguistic meaning. The developed program reflects the logic of the teacher's activities in the formation of a student's personal qualities [participating in subject-subject relations; participating in a joint, discursive practice on the part of all participants, which leads to the active transformation of the students' "Image of the World"; contribution to the development of self-regulation, that is, the capacity for independent problem solving and self-directed activity]. This program is intended by the authors for estimating the accomplished results with the use of any textbook and course in any subject on condition of changing test materials for such a factor attribute as the quality of knowledge in the subject. This teaching methodology is more flexible and means developing a sensitivity to students' current abilities.